Answer:
x = -8
y = 9
Step-by-step explanation:
to solve this expression using simultaneous equation, we would say let
y =9............................................. equation 1
6x + 5y =-3............................................equation 2
substitute equation 1 into equation 2
-3 = 6x + 5y............................................equation 2
6x + 5(9) = -3
6x + 45 = -3
collect the like terms
6x = -3-45
6x = -48
divide both sides by the coefficient of x which is 6
6x/6 = -48/6
x = -8
therefore y = 9
x = -8
At least 4
10% of 12 is 1.2
So 30% is 3.6
And 1% 0.12
So 2% is 0.24
Plus 3.6 onto 0.24 and you get 3.84
Answer:
50
Step-by-step explanation:
3*50=150. 150/5=30 pounds